(untitled) (International Journal of Environmental Sciences, 2025)
Aluminum chloride (AlCl₃) is recognized as neurotoxin that causes oxidative stress (OS), inflammation, and structural damage to the brain, potentially resulting in neurodegenerative conditions. Cerium oxide nanoparticles (CeO₂NPs) exhibited important antioxidant and anti-inflammatory capabilities that may mitigate these effects. The present study is aimed at assessing the histopathological alterations caused by AlCl₃ in brain tissue and the possible protective effects of CeO₂NPs in male albino rats. The rats were randomly dividing into six groups: a control group and five experimental groups, in which two groups receiving CeO₂NPs at two doses of 10 and 100 mg/kg body weight, as well as the other group receiving AlCl₃ (1000 mg/L), and two combined treatment groups receiving AlCl₃ alongside CeO₂NPs at 10 and 100 mg/kg, respectively. Histological sections of brain tissues have been taken and stained with Hematoxylin and Eosin (H&E) to examine histoarchitecture. Furthermore, Masson’s Trichrome (MT) is used to examine fibrosis. Sections stained with H&E revealed that AlCl₃ caused substantial neuronal degeneration, gliosis, and inflammatory infiltration, whereas both dose (10 and 100 mg/kg) with CeO₂NPs, maintained brain architecture and mitigated damage but the effect of the higher dose was greater than the lower one. Sections stained with MT showed more collagen deposition in the AlCl₃ treated group, however those alterations were diminished in nanoparticles treated groups. In conclusion the present study indicated that CeO₂NPs mitigate AlCl₃-induced neurotoxicity and fibrosis in brain tissue, with an increased dosages providing enhanced protection.